Kinetic studies on the peroxyoxalate reaction using environmentally friendly oxalic esters and activators derived from natural products - Bello, Liena Valero (2024)
The peroxyoxalate reaction has been extensively employed in analytical chemistry and, more recently, in bioimaging and photodynamic therapy due to its effectiveness in detecting physiological levels of hydrogen peroxide, a key player in several life-threatening diseases such as cancer. Traditional chemiluminescence studies typically use commercially available oxalate diesters like bis(2,4,6- trichlorophenyl) oxalate (TCPO) or bis(2,4-nitrophenyl) oxalate (DNPO), which are dissolved in volatile, non-biodegradable, and toxic organic solvents. The chemiluminescent by-products of these reactions are carbon dioxide and either 2,4,6-trichlorophenol or 2,4-dinitrophenol, both harmful to aquatic and terrestrial environments. In response to these environmental concerns, new chemiluminescent systems have been developed using oxalic esters synthesized from naturally occurring molecules, such as 2-MCPO (bis(2-(methoxycarbonyl)phenyl) oxalate), FMPO (bis(4-formyl-2-methoxyphenyl) oxalate), and 3-MCPO (bis(3- (methoxycarbonyl)phenyl) oxalate) derived from methyl salicylate, vanillin, and methyl 3-hydroxybenzoate respectively. This study conducts kinetic investigations of the peroxyoxalate reaction using these esters, in anhydrous and aqueous media, employing sodium salicylate or imidazole as catalysts to elucidate the reaction mechanisms. The chemiluminescence parameters were calculated for differentactivators such as 9,10-diphenylanthracene, Rhodamine 6G, and the coumarin derivatives C120, C151, and C153. Additionally, the influence of temperature on the rate constants was examined for 3-MCPO with both salicylate and imidazole as catalysts, subsequently calculating and interpreting the activation parameters from the Arrhenius and Eyring plots. The experimental results revealed specific catalytic behaviors for the two catalysts and provided insights into the reaction mechanisms across different media. Salicylate was found to function as a base catalyst in anhydrous conditions for all three esters in their reaction with hydrogen peroxide. In partially aqueous media, the reaction of 2-MCPO was shown to proceed through specific base catalysis involving salicylate. Both salicylate and hydrogen peroxide participated in the rate-determining step, displaying a first-order dependence for each. Meanwhile, imidazole catalysis revealed distinct pathways: a nucleophilic substitution mechanism for 2-MCPO and FMPO, and for 3-MCPO, a combination of direct base-catalyzed peroxide attack at low concentrations and nucleophilic catalysis at higher concentrations. These findings highlight the nuanced roles of the catalysts and underscore the advantages of salicylate, whose bimolecular rate constants were consistently 4 to 40 times higher than those of imidazole.